Densification process of Merbau (Intsia bijuga) and Matoa (Pometia pinnata J.R. Forster & J.G Forster) Sawdust Waste for Biomass Based Solid Fuel Source in West Papua Indonesia: Optimization using Response Surface Methodology (RSM) - Agus Prasetya; Halomoan Siagian; Felix Arie Setiawan; Himawan Tri Bayu Murti Petrus, S.T., M.E, D.Eng. (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2021)
Merbau (Intsia bijuga) and matoa (Pometia pinnata J.R. Forster & J.G Forster) are two amongst many prominent biomass sources from West Papua, Indonesia. With their versatile characteristics, merbau and matoa wood are used in many industries such as furniture, music instrument, and many other specialty products. However, wood processing industries can emit up to 60% of the residue. In this study, the usage of both merbau and matoa sawdust wastes as solid fuel was studied using response surface methodology (RSM). merbau and matoa sawdust are sieved to get the desired particle size (-20+50 mesh). Two kinds of the sawdust are then mixed in various compositions (70, 50, and 30% merbau). The mixed sawdust is then mixed with varied sticky starch solutions (1, 5, and 10%) to be formed in pellets with various moulding compression force (50, 100, and 150 kg/cm²). The pellets are then analyzed for its characteristics such as ash, moisture contents, and calorific value to be compared with its initial conditions. A full three-level factorial design under RSM was applied to explain the correlation between independent and dependent variables. The results show that statistically, merbau content, binder content, and compressive force showed relatively significant effects on the studied responses (ash content, moisture content, and calorific value). In addition, ANOVA analysis proved that each variable has significant effects on the responses that are confirmed by practically zero P-value. The coefficient of determinations (R²) are all above 0.96 and the normal probability plots confirm that the proposed models adequate the experimental results.Keywords: biomass waste; densification; merbau; matoa; RSM A B S T R A KMerbau (Intsia bijuga) dan matoa (Pometia pinnata Forster) adalah dua di antara sumber biomassa potensial yang berasal dari Papua Barat, Indonesia. Dengan karakteristiknya yang serbaguna, merbau dan matoa digunakan di banyak industri seperti furnitur, alat musik, dan banyak produk khusus lainnya. Namun, industri pengolahan kayu dapat menghasilkan hingga 60% residu. Di Pada penelitian ini, pemanfaatan limbah serbuk gergaji merbau dan matoa sebagai bahan bakar padat dipelajari dengan menggunakan response surface method (RSM). Serbuk gergaji merbau dan matoa diayak untuk mendapatkan ukuran partikel yang diinginkan (-20+50 mesh). Dua jenis serbuk gergaji kemudian dicampur dalam berbagai komposisi (70, 50, dan 30% merbau). Serbuk gergaji yang sudah tercampur kemudian dicampur dengan bahan perekat yang bervariasi larutan pati (1, 5, dan 10%) untuk dibentuk dalam pelet dengan berbagai gaya tekan cetakan (50, 100, dan 150 kg/cm²). Pelet kemudian dianalisis karakteristiknya seperti abu, kadar air, dan nilai kalor untuk dibandingkan dengan kondisi awalnya. Sebuah desain RSM tiga faktorial penuh diterapkan untuk menjelaskan korelasi antara variabel independen dan variabel terikat. Secara statistik, hasil penelitian menunjukkan bahwa kadar merbau, kadar pengikat, dan gaya tekan menunjukkan efek yang relatif signifikan pada respons yang dipelajari (abu kadar air, kadar air, dan nilai kalor). Selain itu, analisis ANOVA membuktikan bahwa masing-masing variabel memiliki efek signifikan pada tanggapan yang dikonfirmasi oleh nilai P yang mendekati nol. Koefisien determinasi (R²) seluruhnya berada di atas 0,96 dan grafik probabilitas normal mengonfirmasi bahwa model yang diusulkan cukup sesuai dengan hasil eksperimen.Kata kunci: limbah biomassa; densifikasi; merbau; matoa; RSM